New Opportunities for Cancer Health Services Research: Linking the SEER-Medicare Data to the Nursing Home Minimum Data Set. Issue 12 (December 2018) - Thomas, Kali S.; Boyd, Eric; Mariotto, Angela B.; Penn, Dolly C.; Barrett, Michael J.; Warren, Joan L.
Abstract : Background: The Surveillance, Epidemiology and End Results (SEER)-Medicare data combine clinical information from population-based cancer registries with Medicare claims. These data have been used in many studies to understand cancer screening, treatment, outcomes, and costs. However, until recently, these data included limited information related to the characteristics and outcomes of cancer patients residing in or admitted to nursing homes. Objectives: To provide an overview of the new linkage between SEER-Medicare data and the Minimum Data Set (MDS), a nursing home resident assessment instrument detailing residents' physical, psychological, and psychosocial functioning as well as any therapies or treatments received. Research Design: This is a descriptive, retrospective cohort study. Subjects: Persons in SEER-Medicare diagnosed with cancer from 2004 to 2013 were linked to the 2011–2014 MDS, with 17% of SEER-Medicare patients linked to the MDS data. During 2011–2014, we identified 318, 617 cancer patients receiving care in a nursing home and 256, 947 cancer patients newly admitted to a total of 10, 953 nursing homes. Of these patients, approximately two thirds were Medicare fee-for-service beneficiaries. Results: The timing from cancer diagnoses to nursing home admission varied by cancer. In total, 93% of all patients were admitted directly to a nursing home from an acute care hospital. The majority of patients were cognitively intact, 21% reported some level of depression, and 9% had severe functional limitations. Conclusions: The new SEER-Medicare-MDS dataset provides a valuable resource for understanding the postacute and long-term care experiences of cancer patients receiving care in United States' nursing homes. Abstract : Supplemental Digital Content is available in the text.